2020
DOI: 10.1001/jamanetworkopen.2020.28195
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes, Costs, and Cost-effectiveness of Strategies for Adults Experiencing Sheltered Homelessness During the COVID-19 Pandemic

Abstract: Key Points Question What are the projected clinical outcomes and costs associated with strategies for reducing severe acute respiratory syndrome coronavirus 2 infections among people experiencing sheltered homelessness? Findings In this decision analytic model, daily symptom screening with polymerase chain reaction (PCR) testing of individuals who had positive symptom screening paired with nonhospital care site management of people with mild to moderate cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 29 publications
3
65
0
Order By: Relevance
“…Background infection rate in the local community of approximately 120 infections/ 1,000,000 person-days. SF, San Francisco Our findings broadly agree with those of two other modeling studies of interventions against COVID-19 in homeless shelters: one in the US [92] and the other in England [93]. The former found that a combination of daily symptom screening with PCR testing of symptompositive individuals, universal PCR testing every 2 weeks, and alternative care sites for those with mild/moderate COVID-19 would significantly reduce infections, while remaining cost-effective, but unlike our analysis did not consider variation in the effectiveness of interventions with community incidence.…”
Section: Discussionsupporting
confidence: 88%
“…Background infection rate in the local community of approximately 120 infections/ 1,000,000 person-days. SF, San Francisco Our findings broadly agree with those of two other modeling studies of interventions against COVID-19 in homeless shelters: one in the US [92] and the other in England [93]. The former found that a combination of daily symptom screening with PCR testing of symptompositive individuals, universal PCR testing every 2 weeks, and alternative care sites for those with mild/moderate COVID-19 would significantly reduce infections, while remaining cost-effective, but unlike our analysis did not consider variation in the effectiveness of interventions with community incidence.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of public health, prevention strategies are needed to minimise the cost of hospitalisation and improve healthcare access among homeless people [ 21 ]. In a modelling study of simulated adults living in homeless shelters, daily symptom screenings were associated with fewer severe acute respiratory syndrome coronavirus (SARS-CoV-2) infections and decreased costs, compared with no intervention [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence quantifying the effectiveness of IPC strategies among PEH was only available from modelling studies, indicating high number of infections (cumulative incidence of 49.3%) if no interventions were taken, even with low SARS-Cov-2 incidence in the general population [54]. Daily symptom screening with PCR testing of individuals who had positive screening results and the provision of alternative care sites for Covid-19 management were modelled to be the most efficient and cost-saving strategy to tackle the pandemic among PEH [65].…”
Section: Discussionmentioning
confidence: 99%